2012
DOI: 10.3109/00016357.2012.715197
|View full text |Cite
|
Sign up to set email alerts
|

Determination of VITA Classical shades with the 3D-Master shade guide

Abstract: Within the limitations of the study, it is usually possible to determine tooth color with the 3D and convert it, via a table, into a VC shade without adding a clinically apparent error to the direct shade match with the VC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Dozic et al corroborate these findings in their study and showed that only a minority of students (2 to 47 %) had been introduced to the methods available for digital shade determination [4] . Based on the Munsell-color-system [5] , the tooth selected for shade matching is compared to a current sample of the color scale (reference) at neutral light conditions [6][7][8] . In Munsell's theory; he described color by terms of hue, value and chroma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dozic et al corroborate these findings in their study and showed that only a minority of students (2 to 47 %) had been introduced to the methods available for digital shade determination [4] . Based on the Munsell-color-system [5] , the tooth selected for shade matching is compared to a current sample of the color scale (reference) at neutral light conditions [6][7][8] . In Munsell's theory; he described color by terms of hue, value and chroma.…”
Section: Methodsmentioning
confidence: 99%
“…Through the determination of lightness (value) in the first level, up to 60 % of incorrect assessment are eliminated. Both further steps, the determination of chroma and hue, reduce color-matching errors with a compliance of almost 70% [6,8] . Clinical studies have demonstrated that the subjective color determination independent of the used color scale, but -in fact -gender-dependent can be learned [9,[10][11][12][13][14] .…”
Section: Methodsmentioning
confidence: 99%
“…It is also the first study to report people's preferences of tooth shade hue and chroma for different skin shades. This study revealed that the most preferred tooth shade for anterior teeth is 1M1 in the 3D Master shade guide, which is equivalent to B1 in the Classic VITA shade guide, 30 regardless of the skin shade of the model and their demographic variables. The CIE average values for L, a and b for 1M1 shade tab were measured in a previous study to be around 86.4 (1.0), -0.4 (0.1), and 10.7 (0.3), respectively.…”
Section: Discussionmentioning
confidence: 82%
“…This study revealed that, regardless of the skin shade of the model and their demographic variables, the most preferred tooth shade for anterior teeth is 1M1 in the 3D Master shade guide, which is equivalent to B1 in the Classic VITA shade guide, 30 and the CIE values of L = 86.4, a = -0.4, and b = 10.7. 25…”
Section: Discussionmentioning
confidence: 84%
“…All the mixtures were formulated to contain a standard loading of inorganic pigments based on metal oxide so that these experimental composites would match the A3 dentin color pattern on the Vita scale [15] . In all preparations, the matrix used belonged to the same production batch, thus avoiding possible changes in composition.…”
Section: Methodsmentioning
confidence: 99%